Symptom burden and quality of life with chemotherapy for recurrent ovarian cancer: the Gynecologic Cancer InterGroup-Symptom Benefit Study. Issue 6 (27th January 2022) - Lee, Yeh Chen; King, Madeleine T; O'Connell, Rachel L; Lanceley, Anne; Joly, Florence; Hilpert, Felix; Davis, Alison; Roncolato, Felicia T; Okamoto, Aikou; Bryce, Jane; Donnellan, Paul; Oza, Amit M; et al.
Abstract : Objective: The Gynecologic Cancer InterGroup (GCIG)-Symptom Benefit Study was designed to evaluate the effects of chemotherapy on symptoms and health-related quality of life (HRQL) in women having chemotherapy for platinum resistant/refractory recurrent ovarian cancer (PRR-ROC) and potentially platinum sensitive with ≥3 lines of chemotherapy (PPS-ROC ≥3). Methods: Participants completed the Measure of Ovarian Cancer Symptoms and Treatment (MOST) and European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire QLQ-C30 questionnaires at baseline and every 3–4 weeks until progression. Participants were classified symptomatic if they rated ≥4 of 10 in at least one-third of symptoms in the MOST index. Improvement in MOST was defined as two consecutive scores of ≤3 in at least half of the symptomatic items at baseline. Improvement in HRQL was defined as two consecutive scores ≥10 points above baseline in the QLQ-C30 summary score scale (range 0–100). Results: Of 948 participants enrolled, 910 (96%) completed baseline questionnaires: 546 with PRR-ROC and 364 with PPS-ROC ≥3. The proportions of participants symptomatic at baseline as per MOST indexes were: abdominal 54%, psychological 53%, and disease- or treatment-related 35%. Improvement was reported in MOST indexes: abdominal 40%, psychological 35%, and disease- or treatment-related 38%. Median time to improvement in abdominal symptoms occurred earlier for PRR-ROC than for PPS-ROC ≥3 (4 vs 6 weeks, p=0.044); median duration of improvement was also similar (9.0 vs 11.7 weeks, p=0.65). Progression-free survival was longer among those with improvement in abdominal symptoms than in those without (median 7.2 vs 2.5 months, p<0.0001). Improvements in HRQL were reported by 77/448 (17%) with PRR-ROC and 61/301 (20%) with PPS-ROC ≥3 (p=0.29), and 102/481 (21%) of those with abdominal symptoms at baseline. Conclusion: Over 50% of participants reported abdominal and psychological symptoms at baseline. Of those, 40% reported an improvement within 2 months of starting chemotherapy. Approximately one in six participants reported an improvement in HRQL. Symptom monitoring and supportive care is important as chemotherapy palliated less than half of symptomatic participants.